Effectiveness of Think Pair Share Learning Model Using Baamboozle Media on Understanding of Science Concepts in Grade V of Elementary School - Hasan Sastra Negara; Niken Amelya Utami (LP2M STIT Palapa Nusantara, 2025)
This study aims to analyze the effectiveness of the Think Pair Share learning model using Baamboozle media on the understanding of science concepts in grade V of Elementary School. The research method uses quantitative with a quasi-experimental research design post-test only control group. The population used was all fifth grade students while the research sample was 40 students in grades VA and VB in elementary schools. Data were collected by observation and testing. Data analysis used prerequisite tests, namely the normality test with Shapiro Wilk, the homogeneity test with Kolmogorov-Smirnov, and the hypothesis test (independent sample t-test) with the help of SPSS version 25. The results showed that the application of the Think Pair Share learning model using Baamboozle media was effective in understanding science concepts in grade V of Elementary School, this was evidenced by the normality test in the experimental class obtaining 0.639 while in the control class obtaining 0.255. Then the homogeneity test obtained is greater than 0.05 and based on the sample t-test test obtained 0.010 so it can be concluded that there is effectiveness in using the learning model using baamboozle media on understanding the concept of IPAS.